2015
DOI: 10.15376/biores.10.3.5845-5862
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Fibre Identification through Color Vectors of Stained Fibre

Abstract: a Simple, rapid staining analytical methods with visual color assessment are the most used in practice, but they involve problems including subjective error, low accuracy, qualitative results, and the necessity of using many kinds of stains and a great deal of morphology information for correct identification. A method of objective fiber identification using color vectors of a microscan from stained fibre digital photography is described in this report. A model set of cellulose fibres was prepared: groundwood;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Sample preparation for the T 401 test is physically laborious and time consuming, requiring boiling, maceration, and acid/base treatments to liberate constituent fibers from a sheet. Finally, the T 401 test results are fraught with multiple sources of imprecision and inaccuracies [2], and liberated fiber samples are also often subject to the effects of atmospheric oxidation once a reagent stain has been applied, making it difficult to archive samples for preservation or specimen banking.…”
mentioning
confidence: 99%
“…Sample preparation for the T 401 test is physically laborious and time consuming, requiring boiling, maceration, and acid/base treatments to liberate constituent fibers from a sheet. Finally, the T 401 test results are fraught with multiple sources of imprecision and inaccuracies [2], and liberated fiber samples are also often subject to the effects of atmospheric oxidation once a reagent stain has been applied, making it difficult to archive samples for preservation or specimen banking.…”
mentioning
confidence: 99%
“…The measurement stopped automatically after equilibrium was reached. A visual coloring test with zinc chloride-iodide [43] confirmed that all three papers under investigation are of rag-type, probably from flax, hemp or cotton.…”
Section: Table 1 Total Areas Of the Mössbauer Spectra Of The Studied Specimensmentioning
confidence: 65%
“…Much of the same information, as already discussed in previous subsections, also can be used as the means of differentiating between different types of fibers Proksch and Keser 1970;Hall 1976;Parham and Gray 1982;TAPPI 1988;Mlynar 1999;Lai 2002;Woodward 2002;Adamopoulos and Oliver 2006;Jablonsky et al 2015). Some of these publications place an emphasis on identification of textile fibers (AATCC Test Method 20, 1990;Lai 2002;Anheuser and Roumeliotou 2003).…”
Section: Fiber Type For Identificationmentioning
confidence: 96%
“…Zhang et al 2013 Color vector analysis was used to achieve more objective and accurate interpretation of staining protocols for fiber identification. Jablonsky et al 2015 Lignocellulosic components' fluorescence spectra were differentiated using conjugated oligothiophenes. Choong et al 2016 Ramie and cotton fibers were differentiated using an iodine reaction.…”
Section: Shi and LI 2013mentioning
confidence: 99%